Transcriptomic responses to coaggregation between oral bacteria / Naresh V R Mutha - Naresh , V R Mutha (2020)
Cell-cell interactions between genetically distinct oral bacteria form macroscopic clumps known as coaggregates. These interactions, termed coaggregation contribute to the formation of highly structured multispecies communities in oral cavity, known as oral biofilms. Individual species also compete and collaborate with other neighboring species through metabolic interactions allowing growth of other species by coaggregation. This study involves the mixing of selected pairs of oral bacteria to form coaggregates and quantifying differential gene expression levels in each pair in comparison with mono-species coaggregation. The dual RNA-Seq approach made it possible to see how bacteria respond to one another leading to different metabolic interactions for each pairing in coaggregation. In this perspective, Streptococcus gordonii was coaggregated with selected oral bacteria. The aim was to analyze transcription data from separate pairings of Streptococcus gordonii with Fusobacterium nucleatum (first pair), Veillonella parvula (second pair) and Streptococcus oralis (third pair) to understand gene regulation mechanisms involved in coaggregation. The data analysis involved comparison of mRNA profiles in mono-species cultures vs coaggregates. Significant differentiallyexpressed genes and pathways in S. gordonii among all three bacterial pairings were compared to determine whether common mechanisms exist between oral bacterial coaggregates analyzed in this study. In the first pairing a total of 119 genes differentially expressed in S. gordonii following coaggregation with F. nucleatum whereas only 16 genes had shown differential expression in F. nucleatum. In both species, genes involved in amino acid and carbohydrate metabolism were strongly affected by coaggregation. In particular, one 8- gene operon in F. nucleatum encoding sialic acid uptake and catabolism was up regulated to 2-5 fold following coaggregation. In S. gordonii, a gene cluster encoding functions for phosphotransferase system-mediated uptake of lactose and galactose was down regulated up to 3-fold in response to coaggregation. In the second pairing a total of 272 genes differentially expressed in V. parvula, including 39 genes in oxidoreductases processes. In S. gordonii, there was a high degree of inter-sample variation. Nevertheless, 69 genes were identified as potentially regulated by coaggregation, including two phosphotransferase system transported and several other genes involved in carbohydrate metabolism. In third pairing a total of 22 genes in S. oralis and 72 genes in S. gordonii were regulated following coaggregation. A 6-gene operon encoding tryptophan in S. oralis was down regulated to 1.5-fold following coaggregation whereas mainly transporter genes in S. gordonii were up-regulated. A large cluster encoding transporters and two component (NisK/SpaK) regulatory system was upregulated to 2-4 folds in coaggregation.